Análise da sustentabilidade de sistemas locais de tratamento de efluentes sanitários para habitações unifamiliares - Martinetti, Thaís Helena (Universidade Federal de São Carlos, 2015)
Sustainability is a recent debate derived from the environmental concern and the use of finite natural resources. Currently, in addition to environmental issues, some authors incorporate the economic, social, cultural and political dimension to its definition. The political dimension emphasizes people participation in decision-making, management and collective control, through the reality understanding and analysis of different alternatives. The adoption of participatory processes for decision-making of more sustainable local systems for residential wastewater treatment enable the knowledge transfer and allows access to unconventional technologies. The sustainability analysis arises from the research and practice in the planning and management areas, as a new tool for decision-making, directed promoting sustainability. This work is inserted in the discussions about concepts, principles, strategies and techniques of more sustainable local system for residential wastewater treatment, emphasizing the interaction between those dimensions. General objective was the sustainability analysis of local systems for residential wastewater treatment, taking into account the multiple sustainability dimensions in view of the territories dynamic balance. General research strategy was the data collection research in technical and scientific literature. General steps were: 1- analysis of the technical and scientific literature regarding studies about the subject; 2- characterization of local alternative for residential wastewater treatment; 3- sustainability analysis of decision-making process for the choice of local alternative for residential wastewater treatment; 4- sustainability analysis of local systems for residential wastewater treatment. To each verified hypothesis, were created a spreadsheet that indicated: the type of information (variable), sources of evidence, the procedures for collecting and analyzing data. Products were: 1-process for decision-making to choose the local system of residential wastewater treatment, principles analysis, actions and strategies for sustainability; 2- synthesis flow for analysis of local treatment of residential wastewater systems and; 3- sustainability analysis of local treatment alternatives and wastewater disposal. Results indicated that the sustainability analysis of local residential wastewater treatment systems helps in the choice and decision-making process. The understanding of the concept and sustainability principles, the use of participation in decision-making, increase the sustainability degree of local residential wastewater treatment systems in the context of the territory dynamic balance. Systems that provide water separation in gray and black ones or systems that do not use water, enable the waste reuse, reduce water consumption and improve participatory process in decision-making at different stages, with management and process social control tend to get gains in sustainability.
Keywords: Engenharia Urbana; Tratamento de efluentes; Planejamento participativo; Sustentabilidade; Dimensões da sustentabilidade; Sustainability; Wastewater treatment; Participatory process; Sustainability dimensions; ENGENHARIAS